1981
DOI: 10.1159/000225553
|View full text |Cite
|
Sign up to set email alerts
|

DNA Distribution Patterns of Preneoplastic Cells and Their Interpretation

Abstract: Gastric mucosa and smears of the cervix uteri – both under normal conditions and in different pathological stages – were processed by flow cytometry. DNA distribution patterns were measured and compared. Special interest was focused on chronic atrophic gastritis (CAG), checking its biological value and clinical importance with the precancerous stages of the cervix uteri. In rare, distinct cases, CAG revealed carcinoma indicating DNA distribution patterns as distinct cases of dysplasia and Ca in situ of the cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Hedley et al [17] and Schutte [16] devised new methods using paraffin-embedded tissue, which have made retrospective studies possi ble and allowed more accuracy. Evidence is now accumulating that DNA aneuploidy is a marker of prognosis in colorectal adenocarci noma as well as in other gastrointestinal tu mors, such as gastric cancer [ 19] and gastroin testinal leiomyosarcoma [20], In the field of colorectal cancer, DNA aneuploidy as mea sured by FCM is present in about 60% of colorectal adenocarcinomas [21][22][23], Studies in premalignant conditions such as ulcerative colitis [12] and chronic atrophic gastritis [24] have shown that DNA aneuploidy can arise prior to the onset of invasive malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Hedley et al [17] and Schutte [16] devised new methods using paraffin-embedded tissue, which have made retrospective studies possi ble and allowed more accuracy. Evidence is now accumulating that DNA aneuploidy is a marker of prognosis in colorectal adenocarci noma as well as in other gastrointestinal tu mors, such as gastric cancer [ 19] and gastroin testinal leiomyosarcoma [20], In the field of colorectal cancer, DNA aneuploidy as mea sured by FCM is present in about 60% of colorectal adenocarcinomas [21][22][23], Studies in premalignant conditions such as ulcerative colitis [12] and chronic atrophic gastritis [24] have shown that DNA aneuploidy can arise prior to the onset of invasive malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Also dormant 'D' cells as described by Darzynkiewicz et al [6] should be taken into con sideration for the explanation of these peaks. The small extra peaks observed in the part of the histo gram which includes cells in S-phasc should also be seen in connection with dormant cells or with phagocytizing cells [37], Summarizing the results presented here and taking the DNA distribution pat tern as a parameter for characterizing and describing the biological value of pathological alteration, we have to attribute an equal biological potential to tu bular and tubulo-villous adenomas. The question re garding the value of an abnormal DNA distribution pattern for prediction of a malignant transformation in a single case remains open.…”
Section: Discussionmentioning
confidence: 62%
“…An only suggested scattering or splitting of the 4C peak was seen in approximately the same frequency (about 20%) in tubular and tubulovillous adenomas without dysplasia. These scattered shapes were also found in cells from chronic atrophic gastric mucosa [37] and gastric mucosal cells originat ing from the surrounding of hyperplastic polyps [25]. The reason for these shapes is supposed to be a nonuniform chromatin structure of the cells collected in these 4C peaks.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The use of gastric endoscopies as a source of cells for cytometric determinations has been reported by other authors (4, 19). In some studies, chronic atrophic gastri-tis has been also discussed (22,23). However, in the latter reports ploidy level and "shape" of the DNA content pattern have been jointly used as cytometric indicators.…”
mentioning
confidence: 95%